217k views
3 votes
Any help is welcome :) only right answers get brainilest

Any help is welcome :) only right answers get brainilest-example-1

2 Answers

4 votes

Explicit rule formula: a(n) = a · rⁿ⁻¹

a(n) = ⁿth term

a = first term

r = common ratio

ⁿ⁻¹ = the previous term

In the recursive rule a₁ = 2/3; aₙ = 9 · aₙ₋₁ the first term is 2/3 and the common ration is 9. We can fill in the explicit formula with what we know.

Thus, the correct answer is [ aₙ = 2/3 · 9ⁿ⁻¹ ]

Best of Luck!

User Dimas
by
5.6k points
4 votes

Answer:


a_(n) =(2)/(3)*9^(n-1)

Explanation:

a1 = 2/3

an = 9*a(n-1)

a2 = 9 *a1 = 9* 2/3

a3 =9*a2 = 9 *(9*2/3) = 9²*2/3

a4 = 9*a3 = 9* (9²*2/3) = 9³*2/3

User Dennis Puzak
by
6.4k points